Implementasi Diversi dan Keadilan Restoratif dalam Sistem Peradilan Pidana Anak di Indonesia - Rosania Paradiaz; Ayu Putriyana; Mawar Putri Octaviani; Dewi Noor Alida (PMIH Untag Semarang, 2026)
The juvenile criminal justice system in Indonesia has undergone a paradigm shift from a retributive to a restorative approach through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), which introduced the concepts of diversion and restorative justice. This study aims to analyze the implementation of the Indonesian juvenile criminal justice system, identify obstacles to the implementation of diversion and restorative justice, and evaluate the fulfillment of children's rights in the judicial process. The research method uses a normative juridical approach with a literature review, analyzing laws and regulations, legal literature, and related secondary data. The results show that although the UU SPPA provides a progressive legal foundation, its implementation still faces serious challenges, including uneven understanding among law enforcement officials, limited infrastructure specifically for children, and suboptimal coordination between institutions. The disparity between das sollen (legal norms) and das sein (empirical reality) remains a fundamental problem in protecting the rights of children in conflict with the law. The study recommends strengthening human resource capacity, improving child-specific infrastructure, optimizing diversion mechanisms, and strengthening inter-institutional coordination to create a juvenile criminal justice system that prioritizes the best interests of children.